2011
DOI: 10.1155/2011/948789
|View full text |Cite
|
Sign up to set email alerts
|

Distance Traveled and Cross-State Commuting to Opioid Treatment Programs in the United States

Abstract: This study examined commuting patterns among 23,141 methadone patients enrolling in 84 opioid treatment programs (OTPs) in the United States. Patients completed an anonymous one-page survey. A linear mixed model analysis was used to predict distance traveled to the OTP. More than half (60%) the patients traveled <10 miles and 6% travelled between 50 and 200 miles to attend an OTP; 8% travelled across a state border to attend an OTP. In the multivariate model (n = 17,792), factors significantly (P < .05) associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 18 publications
1
108
2
1
Order By: Relevance
“…Finally, the issue of geographic barriers to the attendance of community treatment was not addressed. As emphasized by Rosenblum et al (2011), among substance-dependent individuals, lower probability of treatment entry is associated with longer travel distances.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the issue of geographic barriers to the attendance of community treatment was not addressed. As emphasized by Rosenblum et al (2011), among substance-dependent individuals, lower probability of treatment entry is associated with longer travel distances.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the above studies took place in predominantly urban areas (i.e., New York City; Baltimore, Maryland; Oslo, Norway). It is important to examine the efficacy of interim treatment in the rural and suburban areas where access to maintenance can be especially limited (Fortney & Booth, 2001; Havens et al, 2007; Lenardson & Gale, 2008; Rosenblum et al, 2011; Rounsaville & Kosten, 2000; Sigmon, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Neither living closer to a facility nor in an area with more facilities impacted the likelihood of ever having sought or received treatment among our participants. Previous research has shown that the average distance traveled by patients to Opioid treatment programs was 15 miles, sometimes requiring travel across state borders (Rosenblum et al, 2011). It is possible that many of our participants did not seek services at a nearby facility.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since administrative boundaries are arbitrarily drawn and also permeable, individuals are not limited to the services within certain geographies, but instead, often travel across these lines in order to access services or other resources. As mentioned before, evidence has shown that many individuals may travel long distances and sometimes across state boundaries to seek drug treatment services (Rosenblum, et al, 2011). …”
Section: Discussionmentioning
confidence: 99%